A lei de execução penal e sua finalidade ressocializadora : o caso de "Bubu" - Araújo, Tatiana Daré (2012)
One of the issues discussed in the Brazilian penitentiary system is the constant violation of human rights of inmates due to increased crime and violence inside and outside prisons. It is found that the prison system, and state political institution works in a distorted view of their proposed resocializing and below the limits of democracy. Thus, it is evident, in the penal system, the contradiction about the criminal culture that relies on speech for security, while the loss of the monopoly of force by the state underlies the parallel power, with its own codes and standards that coexist with the law officers in the prison. Therefore, it is the aim of analyzing the operation as would prison system from the viewpoint of lawbreakers, and concerns also a systemic approach the arrangement in which are inserted in order to understand how demands and institutional structures, the architecture of space and time criminal, and the rules of the prison influence and shape the individual, to the point of changing their identity and understanding of the universe that surrounds him. He tried to understand the ways in which human rights are seized, reworked and negotiated as a means of survival, where there are three normative codes, either, official rules, extra-legal and disciplinary process that interfere with and reinforce the annihilation prisonization not only the status of citizen, but also the identity of these individuals, the source driving the individuality and reconstruction of self. Thus, the research was based on a comparative analysis on the perception of human rights to the internal dimensions in space and time in prison, two types of prison policies that work antagonistically, ie, the prison where the violation occurs human rights ("Tucum") and where consistent with those rights ("Bubu") in the Criminal Sentencing Act is being implemented. For this purpose, as the object of analysis methodology, the stories of the lives of inmates "Bubu", with the mark clipping oral theme, through the analysis on the spatial and temporal) past: history of previous imprisonment (pass " Tucum "to" Bubu "), b) this: how to identify and highlight the prison officers, employees and directors and c) future: perspectives on life when they leave prison. Thus, we attempted to understand the impacts of the Penal Execution Law Women in Prison Cariacica ("Bubu"), in the process of rehabilitation of inmates. In general, their narratives demonstrate that the proposed rehabilitation of the prison considered a model, has not been answered positively by the internal and responsible for their changes, but the person's own will, which reveals the contradictions and ambiguities of humanitarian policies. Also, in his reports, indicate a need to modify the behavior of prison officials, because of the discipline, rigidity and authoritarian way they are treated, showing the continued oppression and control, making them more angry, humiliated, subjugated and unable to have autonomy. Overcharging of prison in "Bubu" are also perceived by the characterization of being female that is directly linked to the constitution of their subjectivities, in contrast to the prison "Tucum" when the full access to belongings helped them rebuild their individuality, feeling become more happy and free. Finally, the moment you realize close to freedom, they fear a possible mismatch between the world that presents itself as a new, uncertain and challenging. Therefore, the interpretation of the results concludes that both prisons are human rights violators, albeit by different routes.